Dynamic analysis of flat and folded laminated composite plates under hygrothermal environment using a nonpolynomial shear deformation theory. (15th October 2021) - Thakur, Babu Ranjan; Verma, Surendra; Singh, B.N.; Maiti, D.K.
Abstract: In this paper, the effect of the hygrothermal environment on the dynamic analysis of one-fold and two-fold folded laminated composite plates using a nonpolynomial shear deformation theory (NPSDT) is investigated. A computationally efficient C 0 finite element method (FEM) is applied to examine the free vibration characteristic, transient behavior, and steady-state response of laminated composite plates. The formulation employs the total Lagrangian approach for analysis, and the initial stress generated due to hygrothermal load is taken into account through the Green–Lagrange strain displacement relation. The Newmark's method is employed to integrate the spatial–temporal partial differential governing equations. The effect of the thermal environment on the natural frequency of folded and flat composite plates has been illustrated through various examples. The transient displacement and stresses are plotted for various loads. Moreover, transient damped analysis under the thermal load is carried out by considering the Rayleigh damping model. Further, linear harmonic analysis under the hygrothermal environment has also been carried out, and the responses in the neighborhood of natural frequency are plotted. The present model has been compared and validated by the existing literature and the obtained ANSYS APDL solutions, and is found to be performing better for NPSDT.